2020
DOI: 10.1371/journal.pone.0236576
|View full text |Cite
|
Sign up to set email alerts
|

Is the malaria short course for program managers, a priority for malaria control effort in Nigeria? Evidence from a qualitative study

Abstract: Background A Malaria Short Course (MSC) was conceptualized to build the capacity of program managers for malaria control due to the lack of a single comprehensive broad-based programmatic training in Nigeria. Prior to its implementation, a needs assessment was conducted based on the perspectives of stakeholders to plan and develop the curriculum. Methods This was an exploratory qualitative study. Fifty-six purposively selected stakeholders at local, state and national levels were interviewed. Opinions on the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 9 publications
3
10
0
Order By: Relevance
“…Bamiselu et al found sub-optimal adherence to treatment guidelines [ 3 ]. The finding supports that of qualitative study [ 7 ]. Generally, a high priority rating was typical of males and those who were currently working in the malaria program.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Bamiselu et al found sub-optimal adherence to treatment guidelines [ 3 ]. The finding supports that of qualitative study [ 7 ]. Generally, a high priority rating was typical of males and those who were currently working in the malaria program.…”
Section: Discussionsupporting
confidence: 91%
“…Most, at least 70%, rated certain topics and their domains to be of high priority, namely: parasite phases of development, malaria transmission, continuum of malaria control (basic malariology domain), knowledge on treatment guideline, treatment of malaria (malaria treatment domain), vector control, intermittent preventive treatment for pregnant women (malaria prevention domain), mentoring, supervision, and accountability (leadership skills domain), planning activities and using resources, logistics and commodity distribution, and sustainability of malaria control activities (program management domain) and basic statistics domain. The high rating of data sources and data generation, health information system, data analysis and interpretation, data utilization, use of dashboard, use of software, data entry and analysis (surveillance/data management domain) corroborate earlier finding of qualitative a study which suggested the need for data-related training and buttresses the importance of surveillance as a core intervention in the World Health Organization Global Technical Strategy for malaria [ 7 , 9 ].…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations